2010
DOI: 10.1093/jhered/esq018
|View full text |Cite
|
Sign up to set email alerts
|

Extensive MHC Class II B Gene Duplication in a Passerine, the Common Yellowthroat (Geothlypis trichas)

Abstract: The major histocompatibility complex (MHC) is characterized by a birth and death model of evolution involving gene duplication, diversification, loss of function, and deletion. As a result, gene number varies across taxa. Birds have between one and 7 confirmed MHC class II B genes, and the greatest diversity appears to occur in passerines. We used multiple primer sets on both genomic DNA (gDNA) and complementary DNA (cDNA) to characterize the range of class II B genes present in a passerine, the common yellowt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
85
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(96 citation statements)
references
References 104 publications
9
85
1
Order By: Relevance
“…As in other passerines, MHC genes in the common yellowthroat are highly duplicated [41] and our primers amplify multiple loci at once. In this study, a single individual could have up to 18 class I and 46 class II sequences, which implies at least 9 and 23 loci, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As in other passerines, MHC genes in the common yellowthroat are highly duplicated [41] and our primers amplify multiple loci at once. In this study, a single individual could have up to 18 class I and 46 class II sequences, which implies at least 9 and 23 loci, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In terms of similarity (or compatibility), we expected the male mated to a female to possess a relatively lower degree of MHC similarity to the female than males that were not mated to her. We tested these predictions using 454 pyrosequencing, because common yellowthroats have an unusually high number of MHC gene duplications compared with other species [41]. Recent studies indicate that pyrosequencing provides more accurate estimates of MHC variation than older methods for species with high gene copy number [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…MHC genes have been partly characterized in several passerine bird species (Bollmer et al 2010), including the blue tit Cyanistes caeruleus (Schut et al 2011, Wutzler et al 2012. Infection status and infection intensity are complementary measurements of parasite infection.…”
mentioning
confidence: 99%
“…A phylogenetic tree indicated that 15 of the 24 identified alleles either fell into a cluster of putative non-classical sequences (exhibiting limited polymorphisms) or contained stop codons (see Figure S1 in Supplementary Material; Sutton et al 2013). The total number of sequences per individual ranged from 11-23, potentially indicating the simultaneous amplification of 12 MHC class II B loci, a high value that is characteristic of passerine species (Bollmer et al 2010). The number of classical alleles per individual ranged from four to nine; our main MHC analyses focused on these …”
Section: Overall Mhc Diversitymentioning
confidence: 99%